PENERAPAN METODE ACTIVITY BASED COSTING DALAM MENENTUKAN TARIF JASA RAWAT INAP PADA RUMAH SAKIT UMUM UNIVERSITAS MUHAMMADIYAH CIREBON - Surono, Surono; Indriyani, Rinni; Ciptaningsing, Rokhmah Agus; Muzayyanah, Muzayyanah (JURNAL EKONOMI, 2023)
Activity Based Costing method is a method for determining production costs to provide precise and accurate information. This study aims to determine the rate of inpatient services that have been applied by the General Hospital of the Muhammadiyah University of Cirebon and compared with the Activity Based Costing (ABC) method. The data source used is primary data, namely data obtained by direct observation at the Muhammadiyah University Hospital Cirebon and conducting direct interviews with the management and a number of personnel who are related to this research. The data analysis technique that uses in this thesis is by using Activity Based Costing method in determining the tariff for inpatient services at the Muhammadiyah University Hospital Cirebon. The results of the calculation of the activity based costing method at the Muhammadiyah University Hospital Cirebon are: for VIP class Rp.728.953, class I Rp. 427,876, class II Rp. 425,790, and class III Rp. 371,810. The difference between the traditional method and the activity based costing method in the VIP class is a difference of Rp. 328,953, class I Rp. 152.876, class II Rp. 275,790, and class III Rp. 271,810.